SOME NEW OPERATIONS ON INTERVAL-VALUED INTUITIONISTIC FUZZY SOFT SETS - Wang, Jinyan; Tang, Suqin (Italian Journal of Pure and Applied Mathematics, 2015)
Interval-valued intuitionistic fuzzy soft set theory is an intuitionistic fuzzy extension of the interval-valued fuzzy soft set theory or an interval-valued fuzzy extension of the intuitionistic fuzzy soft set theory. In this paper, we further consider interval-valued intuitionistic fuzzy soft sets. Some new operations on interval-valued intuitionistic fuzzy soft sets, i.e., “·”, “+” and Cartesian product, are defined, and some related properties are investigated.